2021
DOI: 10.1088/1741-2552/abebc3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of skull thickness and conductivity on current propagation for noninvasively injected currents

Abstract: Objective. When currents are injected into the scalp, e.g. during transcranial current stimulation, the resulting currents generated in the brain are substantially affected by the changes in conductivity and geometry of intermediate tissue. In this work, we introduce the concept of ‘skull-transparent’ currents, for which the changing conductivity does not significantly alter the field while propagating through the head. Approach. We establish transfer functions relating scalp currents to head potentials in acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In addition, future research is imperative to fully understanding the relationship between conductivity, electric fields and tDCS parameters [85]. A recent study, for example, revealed the current propagation from the scalp to the brain was unaffected by skull conductivity changes [86]. This was found to be due the concept of 'skull-transparency', where using specific current injection patterns without a priori skull conductivity values did not result in large induced field errors, as expected.…”
Section: Age and Peak Induced Fieldsmentioning
confidence: 76%
“…In addition, future research is imperative to fully understanding the relationship between conductivity, electric fields and tDCS parameters [85]. A recent study, for example, revealed the current propagation from the scalp to the brain was unaffected by skull conductivity changes [86]. This was found to be due the concept of 'skull-transparency', where using specific current injection patterns without a priori skull conductivity values did not result in large induced field errors, as expected.…”
Section: Age and Peak Induced Fieldsmentioning
confidence: 76%
“…Current propagation models are designed to analyze, predict, and regulate the electric fields produced in the brain by the applied stimulation. These models consider the impact of different head tissues, their shape, and the specific montages used for stimulation (Holdefer et al, 2006 ; Miranda et al, 2006 ; Russell et al, 2014 ; Huang et al, 2017 ; Forssell et al, 2021 ). Neural activation models provide a detailed understanding of how electric fields generated by stimulation impact the activation of neural tissue at different levels of analysis, ranging from individual cells to the entire brain (Merlet et al, 2013 ; Deco et al, 2019 ; Aberra et al, 2020 ; Meier et al, 2022 ; Tran et al, 2022 ; Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relative power is more sensitive to age‐related changes in EEG bands and normalizes individual differences in skull thickness that may impact absolute power (Marshall et al., 2002). Skull thickness is a main nonfunctional source of variance that may significantly contribute to individual differences in the magnitude of EEG amplitudes and power (Forssell et al., 2021). EEG power spectrum density decreases as the skull thickness increases with age.…”
Section: Discussionmentioning
confidence: 99%